Implementation of an Integrated Curriculum Through Special Class Programs - Muhammad Achsin; Amir Maliki Abitolkha; M. Yunus Abu Bakar (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This study aims to determine how the curriculum's implementation is integrated through a unique class program in Madrasah Aliyah Waru Sidoarjo. This research includes qualitative research. The techniques used in data collection use observation methods, interviews and documentation. As for the data analysis techniques, the authors use qualitative descriptive analysis technique, which is the form of written and unwritten (oral) data from people and behaviours observed. In this case, the author seeks to describe Thoroughly the actual state. This research finds that the integrated curriculum at Madrasah Aliyah Fadlillah Waru Sidoarjo is a curriculum development that eliminates the boundaries between national subjects and TMI subjects. The development of this curriculum can be interpreted as an effort to stir two different curricula in one educational institution. To achieve the institution's goals, in addition to students mastering abilities in general (national) subjects, they can also master abilities in TMI subjects.